2014
DOI: 10.1186/1475-2859-13-89
|View full text |Cite
|
Sign up to set email alerts
|

Production of scopularide A in submerged culture with Scopulariopsis brevicaulis

Abstract: BackgroundMarine organisms produce many novel compounds with useful biological activity, but are currently underexploited. Considerable research has been invested in the study of compounds from marine bacteria, and several groups have now recognised that marine fungi also produce an interesting range of compounds. During product discovery, these compounds are often produced only in non-agitated culture conditions, which are unfortunately not well suited for scaling up. A marine isolate of Scopulariopsis brevic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…The present study revealed that the static condition produced the highest anti-MRSA activity and the activity was decreased with the increment of agitation speeds. The result obtained was in agreement with previous studies that reported the highest production of bioactive compound was obtained under static condition (Bringmann et al, 2007;Tamminen et al, 2014). The favorable effect of air flow on the secondary metabolite production could be attributed to the enhancement of product formation by microorganism under-forced aeration.…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that the static condition produced the highest anti-MRSA activity and the activity was decreased with the increment of agitation speeds. The result obtained was in agreement with previous studies that reported the highest production of bioactive compound was obtained under static condition (Bringmann et al, 2007;Tamminen et al, 2014). The favorable effect of air flow on the secondary metabolite production could be attributed to the enhancement of product formation by microorganism under-forced aeration.…”
Section: Discussionsupporting
confidence: 92%
“…KF525 generally grew as pellets in flasks and inclusion of agar to obtain filamentous growth ( cf. [ 7 ]) appeared to suppress calcaride A production (data not shown). Therefore, bioreactors were inoculated with pre-cultures containing small pellets and the cultures continued to grow as small pellets (1–3 mm diameter).…”
Section: Resultsmentioning
confidence: 87%
“…The casamino acid glucose medium described in [ 10 ] does not supply sufficient nitrogen for all of the carbon to be consumed unless carbon is incorporated into storage compounds or secondary metabolites. The carbon–nitrogen ratio (C/N) of this medium was ~67 (g/g), which was much higher than the level at which nitrogen is expected to limit growth (C/N > 10; [ 7 , 20 ]). A high C/N ratio may be useful to trigger production of secondary metabolites such as the calcarides that do not contain nitrogen, and we continued to use medium with high C/N ratios.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Anti-leukemia active compound of sorbicilactone was produced in lab scale from a static cultur of Penicillium chrysogenum (Bringmann et al, 2007). So it was with cytotoxic compound of scopularide that was produced static culture of fungi Scopulariopsis brevicaulis (Tamminen et al, 2014). Our results suggested that, for emestrin production in large scale, it is necessary to improve culture conditions, such as mixing, aeration, and nutrient source optimation.…”
Section: Emestrin Detection and Concentrationmentioning
confidence: 82%